MODIFIKASI FAMILI METODE ITERASI MULTI-POINT UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Yolla Sarwenda; Imran M.; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses a modified family of multi-p oint iterative method, which is free from second derivative, obtained by mo difying the Chebyshev-Halley-type method. Analytically using Taylor expansion and geometric series, we show that the method has convergence order of three and four. Further by varying the value of the parameter in the formula, we obtain some third order iterative metho ds free secondderivative. Then using some test functions, the prop osed metho d is compared with several known multi-p oint iterative metho ds of order three and four.